MANAJEMEN PEMASARAN PENDIDIKAN DALAM MENINGKATKAN KUANTITAS PESERTA DIDIK DI SMPN 1 KEDUNGPRING LAMONGAN - Choirun Nisa’ Mustofa; Moh Mashudi (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Management is the art or science of managing resources or an activity including the people involved in the activity in order to achieve the stated goals effectively and efficiently, the process of coordinating work activities so that they can be completed effectively and efficiently. Educational marketing is a process by which a person or group gets what they need and want by creating what is needed, offering something they want and broadly being able to transact educational products or services that are of value to others. Educational marketing management is the art or science of offering or selling educational services needed by the community, either individually or in groups, and both parties, both sellers and customers, feel mutually benefited. The existence of marketing management in educational institutions is a form of effort to create a good image of the institution and attract the interest of a number of prospective students. Therefore, marketing must be customer-oriented which in the school context is referred to as students. Marketing management in educational institutions can be carried out through the planning process of educational marketing management, Implementation of Educational Marketing Management and Evaluation of Educational Marketing Management.